CORRELATION AND PATH COEFFICIENT ANALYSIS RELATIONSHIPS IN SAFFLOWER (CARTHAMUS TINCTORIUS L.) - MALI BB; WADIKAR PB; KHANDEBHARAD PR (Innovare Journal of Agricultural Sciences, 2024)
An experiment was conducted on 40 genotypes of safflower (Carthamus tinctorius L.) at the Experimental Farm of College of Agriculture, Latur, to examine genetic diversity and connections among characteristics. In Rabi 2020–2021, the experimental design was a complete randomized block design with two replications. The presence of considerable genetic diversity in the experimental materials was confirmed by analysis of variance results for 10 quantitative characters, which showed significant differences for all traits. The phenotypic and genotypic correlation among the traits and their path analysis were calculated. Plant height, number of branches per plant, number of effective capitulum per plant, number of seed per capitulum, and test weight were found to have a strong positive significant relationship with seed yield. This character had a strong and positive relationship toward seed yield. As a result, these characteristics could be considered important for improving safflower seed yield. The character number of branches per plant, plant height, number of effective capsules per plant, number of seed per capitulum, and test weight showed higher direct positive effects and indirect effects through other components traits. Number of seeds per capitulum had the greatest direct positive effect on seed yield per plant, followed by number of branches per plant and number of capsules per plant. As a result, these characteristics must be considered because they are directly relevant to seed yield. Characters like as days to maturity and oil content showed negative direct effects.